2018
DOI: 10.3892/or.2018.6234
|View full text |Cite
|
Sign up to set email alerts
|

Puerarin inhibits non-small cell lung cancer cell growth via the induction of apoptosis

Abstract: Puerarin, an isoflavone isolated from Kudzu roots, has been demonstrated to have beneficial effect on cardiovascular and cerebral vascular diseases. Recently research has revealed that puerarin exerts an anticancer role in many different types of cancer. The aim of the present study was to investigate the antitumor effects of puerarin on non-small cell lung cancer (NSCLC). Treatment of puerarin significantly inhibited the growth of NSCLC cell lines as determined by CCK-8 kit in vitro. Flow cytometry results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…PR has been reported to possess anti-oxidative, hypotensive and hypoglycaemic activities [13][14][15]. Prior studies have demonstrated that PR exerted protective effects on diabetic kidney injury, heart failure, diabetic cardiomyopathy, cardiac fibroblast proliferation, skeletal muscle energy metabolism and liver lipid metabolism [16][17][18][19][20][21][22]. The hypoglycaemic effect of PR on diabetes mellitus was confirmed by previous studies [15,23,24].…”
Section: Discussionmentioning
confidence: 75%
“…PR has been reported to possess anti-oxidative, hypotensive and hypoglycaemic activities [13][14][15]. Prior studies have demonstrated that PR exerted protective effects on diabetic kidney injury, heart failure, diabetic cardiomyopathy, cardiac fibroblast proliferation, skeletal muscle energy metabolism and liver lipid metabolism [16][17][18][19][20][21][22]. The hypoglycaemic effect of PR on diabetes mellitus was confirmed by previous studies [15,23,24].…”
Section: Discussionmentioning
confidence: 75%
“…Puerarin (20 µM) also inhibited the growth of NSCLC (NCI-H441) cells by inducing apoptosis and autophagy. The mechanism of action involved the inactivation of PI3K/Akt and ERK pathways [185,336].…”
Section: Isoflavonesmentioning
confidence: 99%
“…However, the effects of PUR on apoptosis are different among various kinds of cells. For example, PUR could suppress apoptosis and reduce myocardial injury induced by ischemia [24], while promoting apoptosis in cancer cells [25,26]. Thus, the specific effects of PUR on the fate of NPMSCs in the development of IDD need to be further clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Consisting of the findings in vitro, PUR applied to a rat model was also found to alleviate deformation and structure disorder in vivo with significant activation of p-Akt. However, a few researches reported the anticancerous effect of PUR by inducing apoptosis through inhibiting the PI3K/Akt signaling pathway [26,56,57]. Since most of the conflicting studies were performed on cancer cell lines, it was curious that PUR could perform completely contrary effects on apoptosis in different cell lines.…”
mentioning
confidence: 99%